PATHOLOGICAL EFFECTS OF ARCOBACTER CRYAEROPHILUS INFECTION IN RAINBOW TROUT (ONCORHYNCHUS MYKISS WALBAUM) - Yıldız, H.; Aydın, S. (Acta Veterinaria Hungarica, 2005)
Arcobacter cryaerophilus was isolated from naturally infected rainbow trout (Oncorhynchus mykiss Walbaum), and its pathogenicity was tested by intramuscular injection into 40 healthy 1-year-old rainbow trout at 16 °C. The lethal dosage of 50% end point (LD50) for A. cryaerophilus was calculated 2.25 × 104 viable cells. Experimental infection caused deaths with gross clinical abnormalities such as degenerated opercula and gills, liver damage, haemorrhagic kidney and serous fluid in swollen intestines. The counts of A. cryaerophilus in kidney, liver and gills of experimentally infected fish ranged from 1.59 × 1010 colony forming units (cfu)/g to 7.41 × 1012 cfu/g. The means of erythrocyte (RBC) count, haematocrit level, serum cholesterol, triglyceride, albumin and total protein concentrations in the blood of the experimentally infected rainbow trout group were significantly lower than in the healthy fish. Leukocyte (WBC) counts of the experimentally infected rainbow trout were significantly higher than those of healthy fish. The present work shows that the selected blood characteristics may be good indicators of response to infections in rainbow trout.
Keywords: Arcobacter cryaerophilus, rainbow trout, LD50, leukocyte, haematocrit, cholesterol, triglyceride, total protein, albumin